2009
DOI: 10.1038/nn.2413
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity predicts attitude change in cognitive dissonance

Abstract: When our actions conflict with our prior attitudes, we often change our attitudes to be more consistent with our actions. This phenomenon, known as cognitive dissonance, is considered to be one of the most influential theories in psychology. However, the neural basis of this phenomenon is unknown. Using a Solomon four-group design, we scanned participants with functional MRI while they argued that the uncomfortable scanner environment was nevertheless a pleasant experience. We found that cognitive dissonance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
158
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 49 publications
16
158
0
2
Order By: Relevance
“…Interestingly, the DLPFC, especially on the left side, has been reported to be involved in cognitive dissonance, especially its reduction, in previous EEG studies (21,22). The idea that the DLPFC is involved in conflict resolution rather than conflict monitoring seems to be consistent with the fact that we found stronger DLPFC activations in the present study than was reported previously (18). Whereas subjects had a chance to resolve perceived cognitive dissonance by explicitly stating their new preferences in the present study, there was no such chance during the fMRI scanning in the previous study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Interestingly, the DLPFC, especially on the left side, has been reported to be involved in cognitive dissonance, especially its reduction, in previous EEG studies (21,22). The idea that the DLPFC is involved in conflict resolution rather than conflict monitoring seems to be consistent with the fact that we found stronger DLPFC activations in the present study than was reported previously (18). Whereas subjects had a chance to resolve perceived cognitive dissonance by explicitly stating their new preferences in the present study, there was no such chance during the fMRI scanning in the previous study.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas subjects had a chance to resolve perceived cognitive dissonance by explicitly stating their new preferences in the present study, there was no such chance during the fMRI scanning in the previous study. In other words, it might be the case that while van Veen et al (18) identified brain areas involved in passive emotional reaction to perceived cognitive dissonance (i.e., dACC and anterior insula), brain areas identified in the present study (i.e., dACC and DLPFC) are involved in the active dissonance reduction process following dissonance perception. Nonetheless, these two studies converge to show that the dACC plays an important role in cognitive dissonance; the exact roles played by other areas in the cognitive dissonance process should be further investigated in future research.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations